Evaluative Review: Differences in Knowledge and Perspectives on Generic Drugs Among Health and Non-Health Students - Helza Cahyani; Khue Le Thai Thanh; Umar Muhammad Faisal (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine differences in the level of knowledge and perception about generic drugs among health and non-health students. Methodology:This research uses a quantitative approach with a comparative type. The sample used in this research was 30 health students and 30 non-health students. Sample selection was carried out using random sampling techniques. The data collection method used was a questionnaire. The data analysis technique for this research uses the T-test. Main Findings: Based on the T-test on the level of knowledge and perception about generic drugs in health and non-health students, the results obtained were significance values of 0.048 and 0.041 so it can be concluded that there are differences in the level of knowledge and perception about generic drugs in health and non-health students. Novelty/Originality of this study: This research expands knowledge regarding generic drugs by examining how differences in educational background can influence students' views and understanding of generic drugs, making an important contribution in increasing knowledge about the use of generic drugs among the public.